2008
DOI: 10.1007/s00234-008-0373-y
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion MR imaging for differentiation of benign and malignant meningiomas

Abstract: Introduction Our purpose was to determine whether perfusion MR imaging can be used to differentiate benign and malignant meningiomas on the basis of the differences in perfusion of tumor parenchyma and/or peritumoral edema. Methods A total of 33 patients with preoperative meningiomas (25 benign and 8 malignant) underwent conventional and dynamic susceptibility contrast perfusion MR imaging. Maximal relative cerebral blood volume (rCBV) and the corresponding relative mean time to enhance (rMTE) (relative to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 9 publications
1
55
0
7
Order By: Relevance
“…In the present study, all meningiomas demonstrated increased CBV, a finding similar to what has been reported in the literature. 10 However, not all meningiomas with increased CBV demonstrated tumor stain visible on conventional angiography. Rather, angiographic vascularity was absent in (grade 0) 12.5% of meningiomas and only slightly increased (grade 1) in 18.8% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, all meningiomas demonstrated increased CBV, a finding similar to what has been reported in the literature. 10 However, not all meningiomas with increased CBV demonstrated tumor stain visible on conventional angiography. Rather, angiographic vascularity was absent in (grade 0) 12.5% of meningiomas and only slightly increased (grade 1) in 18.8% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…5 DSC-PWI, on the other hand, measures T2*-weighted signal intensity loss that occurs dynamically over bolus injection of contrast medium, from which relative CBV, a quantitative marker of tumor angiogenesis, can be computed. 6 Both DTI 7,8 and DSC-PWI [9][10][11] had been reported to be useful in subtyping meningiomas. The microvessel area of meningiomas determined by histopathology was found to correlate with relative CBV derived from DSC-PWI.…”
mentioning
confidence: 99%
“…Özellikle yüksek dereceli tümörlerde artmış vaskülarite mevcuttur. Yapılan çalışmalarda tipik ve atipik menenjiomlar karşılaştırıldığında serebral kan hacimleri (rCBV) arasında anlamlı farklılık saptanmamıştır [46][47][48]. Ancak malign menenjiomların peritümöral ödemindeki rCBV değerleri benign menenjiomlardakine göre daha yüksek bulunmuştur [48].…”
Section: Menenjiomunclassified
“…Yapılan çalışmalarda tipik ve atipik menenjiomlar karşılaştırıldığında serebral kan hacimleri (rCBV) arasında anlamlı farklılık saptanmamıştır [46][47][48]. Ancak malign menenjiomların peritümöral ödemindeki rCBV değerleri benign menenjiomlardakine göre daha yüksek bulunmuştur [48]. Bu bulgu da komşu beyin parankimine tümör invazyonuna ve anjiogeneze bağlanmaktadır [49].…”
Section: Menenjiomunclassified
“…In addition to 1 H-MRS, the other advanced MRI techniques, DWI [11] , DTI [12] and PWI have already found increasing use in the evaluation of cerebral tumors and still remain a subject of intense research [1,13,14] . DWI probes local tissue microstructure reflected by the freedom of microscopic motion of water molecules and provides a sensitive means to detect alterations in the integrity of white matter structures, while PWI facilitates the prediction of brain lesion progression in conjunction with histopathology [15] .…”
Section: Even Ifmentioning
confidence: 99%